2004
DOI: 10.1111/j.1365-2141.2004.04964.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse prognostic significance of CD20 positive Reed–Sternberg cells in classical Hodgkin's disease*

Abstract: Summary The prognostic significance of CD20 positive classical Hodgkin's disease (cHD) is uncertain. All cHD cases referred to the Memorial Sloan–Kettering Cancer Center (MSKCC) were retrospectively identified (5/92–11/00); the samples were immunostained, and clinical data ascertained. Cases were re‐reviewed without knowledge of clinical outcome. Univariate and multivariate analyses were performed 248 patients had cHD: 28 CD20+ (11%); 220 CD20−. All clinical characteristics were comparable except haemoglobin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 12 publications
0
31
0
4
Order By: Relevance
“…11,12 In Hodgkin lymphoma, the malignant cells express CD20 of the lymphocyte-predominant subtype, but only in 20%-30% of the cHL subtype. [13][14][15][16] In those cases, rituximab also demonstrated single-agent activity. 17 Emerging data have suggested that rituximab may also have therapeutic value in patients with cHL whose tumors do not express CD20 by either depleting reactive B lymphocytes from the microenvironment, which may enhance antitumor immunity, 18 or by killing the putative CD20-expressing HL stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In Hodgkin lymphoma, the malignant cells express CD20 of the lymphocyte-predominant subtype, but only in 20%-30% of the cHL subtype. [13][14][15][16] In those cases, rituximab also demonstrated single-agent activity. 17 Emerging data have suggested that rituximab may also have therapeutic value in patients with cHL whose tumors do not express CD20 by either depleting reactive B lymphocytes from the microenvironment, which may enhance antitumor immunity, 18 or by killing the putative CD20-expressing HL stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although the prognostic importance of CD20 expression in CHL is still controversial, two independent studies have shown that patients with CD20 + CHL do poorly in clinical trials compared to cases with the classical phenotype (CD20 -CD30 + CD15 + ). 18,19 It should also be noted that, in the light of current knowledge, some of these patients would very probably now be given different diagnoses, including MGZL. The results cannot, therefore, be extrapolated to those obtained with modern standards and used to draw conclusions about the poor prognosis or optimal treatment for MGZL.…”
Section: Diagnostic and Clinical Perspectivesmentioning
confidence: 99%
“…Despite the incorporation of several such parameters in a prognostic model, a sizeable fraction of high-risk patients still could not be identified in one study, 1 underscoring the need for better biomarkers. In this quest, several recent studies have focused on evaluating tissue-specific predictive biomarkers related either to the microenvironment of cHL [2][3][4][5][6][7] or to antigens expressed on the Hodgkin/Reed-Sternberg (HRS) cells [8][9][10] with variable success in identifying patients with poor outcomes, although they warrant validation in larger independent cohorts.…”
Section: Introductionmentioning
confidence: 99%